If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = -13x Solving 5 = -13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13x' to each side of the equation. 5 + 13x = -13x + 13x Combine like terms: -13x + 13x = 0 5 + 13x = 0 Add '-5' to each side of the equation. 5 + -5 + 13x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 13x = 0 + -5 13x = 0 + -5 Combine like terms: 0 + -5 = -5 13x = -5 Divide each side by '13'. x = -0.3846153846 Simplifying x = -0.3846153846
| -3(2x-6)+16=22 | | 5(y-2)-2=2(y+1)+-5 | | 112=48+(2x+4) | | -109+5x=35+x | | 11(-8d+4)= | | -2x+4(1.5x+4)=8 | | 1/5x+6(1/2x+3)=-2 | | -5y=-2x+0 | | -89-7x=5x+187 | | 4x-7=225 | | 3+7x=7x+3 | | 3+12q-14q= | | -20n+68=628 | | 2z=21 | | 6x-78=3x-12 | | -5y-1=11 | | 924=22(v+7) | | 164-2s=6 | | -48+x=23 | | (X-2)+7X=-26 | | 9(h-2)=18 | | -9(x+7)-6=-69 | | x+-47=86 | | 4x+-28=-28+6x | | 4x+11=-3 | | p^2=305 | | 3ab^2+5a^2b-a=2b | | x-(-2)=23 | | 2+7z= | | 5x-180=11x+76 | | 6n-46=3n-7 | | x^3-2ix^2-5x=0 |